2004
DOI: 10.1063/1.1751192
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component droplet growth. II. A theoretical model

Abstract: A droplet growth model is formulated that describes the growth of homogeneous multi-component droplets suspended in a dilute gas-vapor mixture. The droplet is suspended in a real carrier gas, in which the vapors are diluted. The model is applicable for all Knudsen numbers. It is shown that the model can easily be extended to describe the growth of layered droplets. The model calculations are compared to the results of droplet growth experiments of supersaturated water and/or supersaturated n-nonane in methane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They attributed this difference to experimental uncertainty and concluded that the presence of the second vapor did not influence the nucleation of the first, and that co-nucleation did not occur. Multi-component droplet growth in this ternary system was later studied by Peeters et al 8,9 Here, the experiments showed that the presence of water vapor did not affect the growth rate of droplets formed when n-nonane controlled nucleation, while the presence of n-nonane greatly increased the growth rate of droplets when water controlled nucleation.…”
Section: Introductionmentioning
confidence: 90%
“…They attributed this difference to experimental uncertainty and concluded that the presence of the second vapor did not influence the nucleation of the first, and that co-nucleation did not occur. Multi-component droplet growth in this ternary system was later studied by Peeters et al 8,9 Here, the experiments showed that the presence of water vapor did not affect the growth rate of droplets formed when n-nonane controlled nucleation, while the presence of n-nonane greatly increased the growth rate of droplets when water controlled nucleation.…”
Section: Introductionmentioning
confidence: 90%